Sinusoidal PWM Techniques Comparison for the Quasi-Y-Source Inverter - Santos, Rafael [UNESP]; Gonçalves, Flávio A. S. [UNESP] (Springer Nature, 2021)
Impedance network inverters (INIs) have emerged as an alternative to improve traditional inverters, allowing their operation as a buck-boost-type converter, through the utilization of the “shoot-through” conduction state, where switches of one or more inverter legs are gated on simultaneously. Recently introduced, the quasi-Y-source inverter (QYSI) is a INI with magnetic coupling, which has particular operational advantages, specially for renewable sources and distributed generation. To control the QYSI, there are several techniques based on sinusoidal pulse width modulation (SPWM), which are modified to allow the shoot-through state. This work aims to present, through theoretical, simulations and experimental results, a comparative analysis of three SPWM techniques applied in three-phase QYSI, considering a fixed inverter gain factor and a three-phase/three-wire wye-connected R load to the inverter output after a LC filter. The following modulation techniques were compared: simple boost control (SBC), maximum boost control with third harmonic injection (MBC3h) and maximum constant boost control with third harmonic injection (MCBC3h). A comparative analysis was performed showing several relationships among voltage gain, switch voltage stress, shoot-through duty ratio and converter design, for the different SPWM techniques. It is shown the advantages and disadvantages of each SPWM technique applied to QYSI, and merit indexes are indicated in order to help to establish proper criteria for choosing among SPWM techniques for three-phase/three-wire power system applications.
Keywords: Distributed generation; Impedance networks; Inverter; Quasi-Y-source; SPWM